ROLE OF INDRIYA IN COGNITION AS EXPLAINED IN AYURVEDA WITH REFERENCE TO RECEPTORS (International Journal of Ayurveda and Pharma Research, 2020)
Cognitive impairments is a silent issue which is imparting a lot of burden over society now-a-days. Intellectual and emotional dysfunctions are another story which are displayed by the virtue of poor dietary regimen where the concept of – Tan mana bhunjita is neglected. The Sharir and Indriya are feed with adultered things with an extensive variety of distractions today. This altogether is misleading the cell signaling mechanics of body affecting the perception through by – Asatmyendriyarthasamyoga. Ayurveda has deep roots in the process of learning or cognition which mainly depends on the Indriyarthasannikarsha. Indriya, for the sense of objective understanding, here are justified with variety of receptors in terms of their functional capacities. The concept of Indriya and knowledge learning process is much more beyond the present concept of receptors and neural biochemistry. Specificity of receptors within the body with various morphological and functional responsibilities can be graded to understand the intellectual concepts of Indriya from gross to subtle level, such as- Sukshma, Sukshmatara and Sukshmatama. Indriyapanchapanchak is one such concept in Ayurveda where the specificity of receptors, its respective pathways and neural centers for perception of knowledge are easily understood and efforts for the same are highlighted through this topic.